2021
DOI: 10.3390/app11041813
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Medicinal and Aromatic Plants to Engineered Nanoparticles

Abstract: Medicinal and aromatic plants have been used by mankind since ancient times. This is primarily due to their healing effects associated with their specific secondary metabolites (some of which are also used as drugs in modern medicine), or their structures, served as a basis for the development of new effective synthetic drugs. One way to increase the production of these secondary metabolites is to use nanoparticles that act as elicitors. However, depending on the specific particle size, composition, concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 259 publications
0
11
0
Order By: Relevance
“…The content of secondary metabolites in plants is closely related to environmental stresses, as secondary metabolites are involved in plant defense against environmental stresses. 42 Previous Environmental Science: Nano Paper reports suggested that NMs triggered oxidative responses and regulated the expression of secondary metabolites synthesis proteins, 10 which may effectively enhance the medicinal active ingredients of BLG. Therefore, we further examined the antioxidant system of BLG in response to the degree of plant stress (Fig.…”
Section: Impacts Of the Nanomaterials On The Antioxidant Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The content of secondary metabolites in plants is closely related to environmental stresses, as secondary metabolites are involved in plant defense against environmental stresses. 42 Previous Environmental Science: Nano Paper reports suggested that NMs triggered oxidative responses and regulated the expression of secondary metabolites synthesis proteins, 10 which may effectively enhance the medicinal active ingredients of BLG. Therefore, we further examined the antioxidant system of BLG in response to the degree of plant stress (Fig.…”
Section: Impacts Of the Nanomaterials On The Antioxidant Systemmentioning
confidence: 99%
“…9 Using NMs as inducers for increasing plant metabolite production is becoming an emerging approach. 10 The application of NMs may lead to a direct increase in plant production or an indirect increase in the synthesis and accumulation of secondary metabolites by stimulating the stress system of the plant. 11,12 Among the various NMs studied, multi-walled carbon nanotubes (CNTs) and iron oxide nanoparticles (Fe 2 O 3 NPs) are considered as potential candidates for enhancing plant growth, defense systems, and metabolic acceleration with less toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, the emergence and combination of nanotechnology to drug discovery has proven quite beneficial [221]. Reports indicate that the use of nanoparticles of perlite, perlite-TiO 2 , multi-walled carbon nanotubes (MWCNTs), and MWCNT-COOH, among others, result in the improved yields of secondary metabolites from plants such as Hypericum perforatum L. (Hypericaceae), Salvia verticillata L. (Lamiaceae), Catharanthus roseus (L.) G.Don (Apocynaceae), and Salvia nemorosa L. (Lamiaceae) [222]. Additionally, silver nanoparticles increased the production of tryptanthrin in Isatis constricta P.H.…”
Section: Application Of Nanotechnologymentioning
confidence: 99%
“…More than a half of all small-molecule-approved drugs between 1981 and 2014 belong to groups of natural products or mimic natural products [1]. Many plant secondary metabolites [2] have also been used as model compounds for the subsequent development of synthetic drugs [3][4][5][6]. One such example is a cinnamic acid and its derivatives, e.g., coumaric acids, caffeic acid, ferulic acid or sinapic acid, which are widely distributed in many plants and assure their many physiological processes.…”
Section: Introductionmentioning
confidence: 99%